Kardiochirurgia dorosłychChirurgiczne leczenie rozwarstwienia aorty typu A z wszyciem protezy aorty wstępującej, wymianą łuku aorty i jednoczasową śródoperacyjną implantacją wewnątrznaczyniowej protezy aorty zstępującej - Brykczyński, Mirosław; Biskupski, Andrzej; Mokrzycki, Krzysztof; Waligórski, Szymon (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Aortic dissection affecting the ascending part of the aorta together with the arch and descending part (Stanford type A) is a disease with very serious prognosis. An increase in number of patients referred for surgical treatment is noted in recent years, which is due to the progress in diagnostic imaging. A double stage or a very extensive single stage surgery is a conventional method of treatment of this disease. The introduction of stent grafts has made a less invasive way of treatment possible. We present a case of a 54-year-old woman with an A type aortic dissection who had simultaneous replacement of the ascending aorta and aortic arch and implantation of an Evita stent graft into the descending aorta.